2019
DOI: 10.21859/ijpn-06062
|View full text |Cite
|
Sign up to set email alerts
|

Predicting of Nursing Students’ Eating Disorder based on Alexithymia, Coping Styles and Cognitive Emotion Regulation

Abstract: Introduction: In recent years, the eating disorder as a psychosocial disorder has increased dramatically and this disorder has an important role in reduction of physical and mental health. This research aimed to predicting of nursing students' eating disorder based on alexithymia, coping styles and cognitive emotion regulation. Methods: This study was a descriptive from correlational type. The research population was the nursing students' of Islamic Azad University of Ahvaz branch in 2017-18 years which from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Also, individuals with good well-being often experience positive emotions, are optimistic about events (even stressful ones), and use more healthy coping strategies (Heintzelman & Diener, 2019;Satici et al, 2021). In this regard, studies show that social media addiction has a negative and significant relationship with psychological well-being (De Lenne et al, 2018;Sharma & Sharma, 2018;Arabi et al, 2021). A study also showed that Instagram addiction negatively and significantly affected psychological well-being (Sharifi Fard et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Also, individuals with good well-being often experience positive emotions, are optimistic about events (even stressful ones), and use more healthy coping strategies (Heintzelman & Diener, 2019;Satici et al, 2021). In this regard, studies show that social media addiction has a negative and significant relationship with psychological well-being (De Lenne et al, 2018;Sharma & Sharma, 2018;Arabi et al, 2021). A study also showed that Instagram addiction negatively and significantly affected psychological well-being (Sharifi Fard et al, 2022).…”
Section: Introductionmentioning
confidence: 99%